Analisis Prosedur Pengiriman Barang Pada Perusahaan Eksportir - Jaelan, Ahmad; Nabilah Rahmasari, Dinda; Claudya Ramad, Findi; Nurhalizah, Marshanda Rahmatillah; Bernanda Alyansa, Refi; Putra Indonesia, Tegar; Bhakti Utami, Rachma (Jurnal Administrasi Profesional, 2024)
Analysis of goods delivery procedures at exporting companies is an important key in optimizing the supply chain and ensuring operational efficiency. This research aims to analyze the export shipping procedures implemented by PT. Supra Aluminum, a company engaged in the production and distribution of aluminum products. In the export shipping process, there are several stages that must be passed to ensure the product reaches international consumers safely and on time. This study uses a qualitative descriptive method, collecting data through interviews, observation and analysis of company documents. The research results show that PT. Supra Aluminum has implemented systematic delivery procedures, starting from preparing export documents, checking product quality, selecting delivery methods, to monitoring delivery. However, there are several obstacles faced, such as delays in processing documents and communication problems with related parties in the destination country. This research provides valuable insights for exporting companies in improving their goods delivery processes, increasing reliability, and reducing overall operational costs.